1993
DOI: 10.1152/ajpgi.1993.265.2.g214
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase induction and intestinal epithelial cell viability in rats

Abstract: The present study determined the presence of constitutive and inducible nitric oxide (NO) synthase activities in intestinal isolated epithelial cells and the effects of NO induction on intestinal epithelial cell viability. Epithelial cells were isolated from rat proximal small intestine by dispersion using citrate and EDTA. Constitutive NO synthase activity, determined by [14C]arginine conversion to citrulline that was inhibited by in vitro incubation with the arginine analogue NG-monomethyl-L-arginine (L-NMMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
113
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 0 publications
6
113
1
Order By: Relevance
“…Based on the use of inhibitors of NO synthase (Rees et al, 1990;Moore et al, 1990) such as NG-monomethyl L-arginine (L-NMMA) or N0-nitroarginine (L-NOARG), NO has been proposed as a mediator of the non-adrenergic, non-cholinergic (NANC) relaxation of the intestinal smooth muscle, including that of rat or guinea-pig stomach and duodenum and the canine ileo-cecal juction and duodenum (Li & Rand, 1990;Bult et al, 1990;Toda et al, 1990;Desai et al, 1991;Irie et al, 1991). In addition, NO synthase has been located in the myenteric plexus and other neuronal structures of the rat gastro-intestinal tract (Bredt et al, 1990;Belai et al, 1992), although the contribution of the nitrergic neuronal enzyme to the overall NO synthase activity in the gastrointestinal tissues is not yet fully clear (Whittle et al, 1992;Grider et al, 1992; Sanders & Ward, 1992;Tepperman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the use of inhibitors of NO synthase (Rees et al, 1990;Moore et al, 1990) such as NG-monomethyl L-arginine (L-NMMA) or N0-nitroarginine (L-NOARG), NO has been proposed as a mediator of the non-adrenergic, non-cholinergic (NANC) relaxation of the intestinal smooth muscle, including that of rat or guinea-pig stomach and duodenum and the canine ileo-cecal juction and duodenum (Li & Rand, 1990;Bult et al, 1990;Toda et al, 1990;Desai et al, 1991;Irie et al, 1991). In addition, NO synthase has been located in the myenteric plexus and other neuronal structures of the rat gastro-intestinal tract (Bredt et al, 1990;Belai et al, 1992), although the contribution of the nitrergic neuronal enzyme to the overall NO synthase activity in the gastrointestinal tissues is not yet fully clear (Whittle et al, 1992;Grider et al, 1992; Sanders & Ward, 1992;Tepperman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary accounts of this work have been presented in abstract form (Whittle et al, 1993;Martinez-Cuesta et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we have demonstrated that the enterocyte injury caused by C. sakazakii appears to be dependent on the production of NO, as inhibition of inducible NO synthase (iNOS) by small interfering RNA (siRNA) prevented apoptosis of IEC-6 cells (19). Although LPS has been shown to increase iNOS expression in the ileum of mice colonized with bacteria (21,22), no studies to date have addressed how OmpA interaction with intestine induces NO.…”
mentioning
confidence: 99%
“…It was considered that nitric oxide derived by this isoform of NOS was injurious to the gastrointestinal mucosa. 47,48 However, this concept was recently challenged by studies in which a protective effect of iNOS on gastric mucosa injury induced by ethanol,¯urbiprofen or water-immersion-restraint stress was reported. 49±51 Although the protective action of nitric oxide through this isozyme is still uncertain, nitric oxide produced from iNOS in the microvasculature and maintenance of blood ow was proposed.…”
Section: Discussionmentioning
confidence: 99%